Peningkatan Produksi Semen Ayam Kampung Melalui Suplementasi Daun Kelor (Moringa oleifera) - Heru Suripta; Puji Astuti (AGRISAINTIFIKA: Jurnal Ilmu-Ilmu Pertanian, 2021)
AbstractRural chickens are widely developed by artificial insemination methods, so good quality semen is needed so that fertility and hatching eggs are high. Moringa is famous as a "miracle" plant that contains high and complete nutrients. This study was conducted to examine the effects of moringa oleifera supplementation on chicken semen production. In this study used roosters aged about 1 year weighing an average of 2.0 kg as much as 15 tails divided into 5 treatments, each 3 repeats, each repeat consists of 1 tail. The first group of chickens were used as controls, not given treatment, only given basal feed (T0). The second group of chickens were given 1 gram of moringa leaf powder, every day (T1), group 3 chickens were given 2 grams of moringa leaf powder per day (T2). Furthermore, chickens in group 4 (T3) were given moringa leaf extract supplements of 0.1 ml per head per day were smoked daily and the 5th group (T4) was given moringa extract supplements as much as 0.2 ml were smoked daily. The variables observed were the volume of semen, the number of spermatozoa, motility, live sperm, sperm mass movement, color, viscosity and pH of the semen. Semen volume, the number of spermatozoa, motility and percentage of live sperm were analyzed with variance analysis using the spss series 25 program, while viscosity, color and pH were reported in a descriptive analysis. The results showed that chickens supplemented moringa leaves in powder form as much as 2 grams per day (T2) and extract as much as 0.2 ml per day (T4), showed a significant increase in cement volume (0.45±0.01 ml) (P<0.05) compared to the volume of cement in chicken control which was only 0.29±00.07ml. Likewise, the concentration of spermatozoa, motility, live spermatozoa and movement of spermatozoa mass showed improvement in quality, but had no effect on the color, consistency and pH of semen. It can be concluded that supplementation of moringa leaves, both in the form of powder and extract can increase the production of chicken cement. Key words: Moringa oleifera, rural chicken, semen production